2023
DOI: 10.1088/1751-8121/acd091
|View full text |Cite
|
Sign up to set email alerts
|

Quantum coherence as asymmetry from complex weak values

Abstract: Quantum coherence as an asymmetry relative to a translation group generated by a Hermitian operator, is a necessary resource for the quantum parameter estimation. On the other hand, the sensitivity of the parameter estimation is known to be related to the imaginary part of the weak value of the Hermitian operator generating the unitary imprinting of the parameter being estimated. This naturally suggests a question if one can use the imaginary part of the weak value to characterize the coherence as asymmetry. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…Our results thus strengthen the quantitative link between the quantumness which manifests in the nonclassical values of KD quasiprobability, the associated strange weak value, and quantum contextuality, to the nonclassicality captured by the concept of quantum state subjected to measurement in the forms of asymmetry [64,65], general quantum correlation [66], and uncertainty relation [67]. These results motivate the search for a quantitative connection between KD nonclassicality and strange weak value to quantum entanglement.…”
Section: Discussion and Remarkssupporting
confidence: 76%
“…Our results thus strengthen the quantitative link between the quantumness which manifests in the nonclassical values of KD quasiprobability, the associated strange weak value, and quantum contextuality, to the nonclassicality captured by the concept of quantum state subjected to measurement in the forms of asymmetry [64,65], general quantum correlation [66], and uncertainty relation [67]. These results motivate the search for a quantitative connection between KD nonclassicality and strange weak value to quantum entanglement.…”
Section: Discussion and Remarkssupporting
confidence: 76%
“…Remarkably, the nonreality and/or the negativity of the KD quasiprobability is tighter than noncommutativity [37,38]. Significant works over the past decade showed that KD quasiprobability and its nonclassical values play crucial roles in quantum tomography [39][40][41][42], quantum metrology [43][44][45], quantum thermodynamics [45][46][47], a wide spectrum of quantum fluctuations in condensed matter physics [48], information scrambling in many body quantum chaos [49,50], in quantum foundation to prove quantum contextuality [51,52], and recently in the characterization and quantificiation of coherence and asymmetry [53][54][55].…”
Section: Introductionmentioning
confidence: 99%